Incidence and Extent of Substance Abuse among Secondary School Students in Nairobi Province, Kenya: Implications for Specialized Intervention - King’endo, Madrine (Kenyatta University, 2010)
Substance abuse has become a major challenge in secondary schools in Kenya. A study carried out in Kenya observed that 20% of adolescents aged between 12 and 22 years smoke cigarettes, 9% smoke bhang while 23% drink commercial beer and spirits. This is the age in which most youths are in schools and colleges. The aim of this study was to find out the incidence and extent of drug abuse among secondary school students in Nairobi Province, Kenya. This information is useful in developing specialized educational programs for drug abuse in Kenya. The objectives of this study were: to determine various substances commonly abused by students, assess the prevalence of substance abuse in secondary schools, determine the factors that contribute to substance abuse, students‘ behaviour related to substance abuse and identify the factors that influence students to abuse drugs. An expost-facto research design was employed. The study population comprised of all public secondary schools in Nairobi Province. The sampling was done using stratified sampling to obtain different categories of schools, and the status of each school. The schools were chosen from the strata using purposive and simple random sampling methods. Systematic sampling was then applied to obtain the required number of students, where every tenth student from the admission register was selected. One counselling teacher from each sampled school was selected to participate in the study. The total number of respondents was 525 students and 14 counselling teachers. A separate questionnaire for students and another one for counselling teachers were used to collect data. The instrument‘s validity and reliability was enhanced through a pilot study in two schools within the province and were not included in the main study. Face validity and content validity was used by the researcher engaging colleagues and experts in the school of education. The questionnaires were administered to the respondents by the researcher assisted by four research assistants. The research began after obtaining a research permit from the Ministry of Education. The data obtained was coded and analysed using the SPSS programme for windows. The statistics used for this exercise were mainly percentages, pie charts and bar graphs. However, the stated hypotheses were tested by the use of the chi square. The key findings showed that peer pressure, school and family stress, and drug availability contributed to students‘ drug abuse. It was also found that alcohol was the most abused drug, that boys abused drugs more than girls and that drug abuse was more prevalent in mixed schools than the other categories of schools. The study also found that most students, 81%, who abused drugs did this often. The study concludes that stringent measures should be put in place urgently so as to address the problem of drug abuse. The study recommends a multifaceted approach as a strategy for minimizing the vice in the Kenya secondary schools.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Doctor of Philosophy (PhD) in the School of Education, Kenyatta University October, 2010